Paternal abandonment associations and socioeconomic factors on language development (Research, Society and Development, 2021)
Language development depends on the interaction of biological, environmental and psychosocial factors existing in the different contexts in which children are inserted. Objective: To evaluate the association of paternal abandonment and socioeconomic factors on the language development of children in a public day care center in the city of Marabá (PA). Method: This is a study of character transverse, carried out with 62 children from 3 to 6 years old. The instruments used were the Poverty Level Measurement Instrument and the Denver II Developmental Screening Test. Statistical analysis the ram used are the tests are Qui-quadrado, Test G and Test U, all with a significance level of 5%. Results: As for the level of poverty, 55 (88.70%) children had a higher low income and 13 (20.97%) children had suspected language delay. Twenty-five (89.30%) children, whose parents worked per job, had questionable outcome. And, 11 (39.30%) children who have been abandoned entirely by s father s had questionable results in the language. Conclusion: Social variables such as paternal abandonment and socioeconomic factors have a direct influence on child language development.